Profiling biopsychosocial health of cancer-diagnosed elderly in Italy by Passi d'Argento, 2016-2017. (30th September 2020) - Contoli, B; Minardi, V; Possenti, V; Carrozzi, G; Cristofori, M; D'Argenzio, A; De Luca, A M C; Ramigni, M; Trinito, M O; Masocco, M
Abstract: Background: PASSI d'Argento (PdA) is an Italian population-based surveillance system, coordinated by the Istituto Superiore di Sanità (ISS) and carried out by the Local Health Units (LHUs). PdA monitors wide-ranged health related-behaviours in the elderly (65+) living in Italy as per the three pillars of the "Active Healthy Ageing" framework: Health, Participation, Security. Methods: The PdA sample is randomly selected from the LHU lists, stratified by sex and age. 22, 811 records have been collected in 2016-2017 on a representative sample of residents aged over65, not being hospitalised, in long-term care, in a nursing home or prison. Results: 3, 019 respondents resulted cancer-diagnosed elderly (CDE) reporting cancer diagnosis or confirmation, leukaemia and lymphomas included (annual average prevalence of 12.8%, Confidence Intervals 95%: 12.1-13.4%; one million and 729 thousand people). CDE refer: poorer health conditions (22%) than Chronic Elderly Patients (CEP; 18%) and Healthy Elderly (HE; 5%), sight impairment (12%), hearing loss (15%) and chewing problems (14%). CDE (10%) and CEP (11%) are more prone to fall than HE do (6%). Disability accounts for 21% in CDE and CEP vs. 12% in HE. A multivariate analysis confirms a compromised psychophysical health profile in CDE vs. HE, and vs. CEP. CDE behave still unhealthily, are insufficiently advised by health professionals, do not comply with the seasonal flu vaccination [Health]. CDE face increased risk for isolation or cognitive decline: they experience lower social connectedness (17%) than CEP (20%) and HE (28%) [Participation], and perceive higher neighbourhood insecurity (19%) than how CEP (17%) and HE (13%) do [Security]. Conclusions: PdA data on the poor biopsychosocial health profile of CDE highlight to what extent healthy behaviours and prevention can ameliorate their quality of life PdA calls for global action strategies in Italy, which aim at taking complete charge of CDE and also CEP. Key messages: In Italy, elderly cancer survivors show poor biopsychosocial health profile and overall quality of life. By modifying behaviours, elderly suffering from any cancer or chronic disease can age healthily.